AGGRESSIVE BEHAVIOR IN CHILDREN - PSYCHOCORRECTION WORKS USED IN ELIMINATING THE BEHAVIOR - Dilorom Abdullayevna Saliyeva,; Mukhammadrizo Juraboyev, (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, the causes of aggressive behavior in children and the content of psychocorrective work used to eliminate it, methods of using art therapy, isotherapy (by drawing, projective method), making things (from plasticize, clay, dough), music therapy, fairy-tale therapy, special information about the use of targeted therapies.